Rethinking the bioethical consequences of monism and dualism: Systemic emergentism as an epistemic perspective that overcomes totalitarianism - López Muñoz, Francisco; Pérez Fernández, Francisco (Acta Bioethica, 2020)
For centuries, the understanding of conciousness has been one of the topic issues of intellectual development, and a context in which the different sociocultural, scientific, philosophical and ideological perceptions of the human being have been defined and redefined. Far from being a solved problem, it’s a theme that, reformulated again and again in different fields and contexts, returns endlessly to the epicenter of intellectual discussion because it has, necessarily, trascendental epistemic and ethical consequences. This paper tries to show how such confrontation and its positions are fed by an “outdated” perception of the problem, when faced it from an essentialist perspective (encrypted on a model of thought based on reason-object schemes). Therefore is proposed a reformulation of the question in procedural terms inspired by the theory of systemic emergentism. So, it is intended to provide an overcoming approach to an intellectual model that is considered obsolete, while fostering an ethical reflection on the ideological intellectual consequences and practices derived from its artificial support in the field of Science.